Impact of Social Media Marketing Activities on Brand Loyalty: Exploring the Mediating Role of Brand Awareness and the Moderating Influence of Customized Age Group and Social Media Influencer - Qureshi, Farhan Khurshid; Tahir, Naeem Ahmed (Journal of Development and Social Sciences, 2025)
The proposed study intends to investigate the influence of Social Media Marketing Activities (SMMA) on brand loyalty through mediating role of brand awareness and moderating effects of customized age groups and social media influencers. As social media has become a major marketing medium, organizations need to comprehend the effect the social media sites like Instagram, Facebook and Twitter have on consumer behavior and loyalty particularly in emerging markets and among them is Pakistan. The use of structured questionnaires involved the sample data of 260 of the social media individuals in Rawalpindi and Islamabad. Descriptive statistics was performed on the quantitative data using SPSS and Structural Equation Modeling (SEM) to examine whether relations clarified in hypotheses were present and also to test the Structural relationship of fit. Findings showed that SMMA has a positive effect on brand loyalty and that brand awareness has a huge role of mediation. As well, the effect of SMMA on awareness and loyalty was modulated by customized age groups and by popularity on the social media. Marketers are advised to employ age group-specific information and reputable ambassadors that will enhance brand consumption and loyalty.